Some of the main factors of innovative renewal of companies' operations - Hustič, Igor (Organizacija (Kranj), 2010)
Problems cannot be solved by the mentality that has caused them, such as neglecting the non-technological innovation. Often, innovative renewal of companies' operations is urgently needed. Overcoming the consequences of the global economic and financial crisis cannot be successful without innovation of the values, culture, business ethics and norms of all their important stakeholders. We suggest a new synergy of methods aimed at renewal of business processes in an innovative way by using the dialectical systems theory approach. We combine BSC, ISO 9000, the method 'learning company' and USOMID. Literature so far has not made it clear that those approaches can complement each other and jointly contribute to renewal of business operations according to the requirement of the requisite holism.
Keywords: management; podjetja; poslovni proces; inovativnost